Autophagy, a Novel Pathway to Regulate Calcium Mobilization in T Lymphocytes - Jia, Wei; He, Mingxiao; He, You-Wen; Mcleod, Ian (Frontiers in Immunology, 2013)
The T lymphocyte response initiates with the recognition of MHC/peptides on antigen presenting cells by the T cell receptor (TCR). After the TCR engagement, the proximal signaling pathways are activated for downstream cellular events. Among these pathways, the calcium-signaling flux is activated through the depletion of endoplasmic reticulum (ER) calcium stores and plays pivotal roles in T cell proliferation, cell survival, and apoptosis. In studying the roles of macroautophagy (hereafter referred to as autophagy) in T cell function, we found that a pathway for intracellular degradation, autophagy, regulates calcium signaling by developmentally maintaining the homeostasis of the ER. Using mouse genetic models with specific deletion of autophagy-related genes in T lymphocytes, we found that the calcium influx is defective and the calcium efflux is increased in autophagy-deficient T cells. The abnormal calcium flux is related to the expansion of the ER and higher calcium stores in the ER. Because of this, treatment with the ER sarco/ER Ca2+-ATPase pump inhibitor, thapsigargin, rescues the calcium influx defect in autophagy-deficient T cells. Therefore, autophagy regulates calcium mobilization in T lymphocytes through ER homeostasis.